Rancangan Program Simulasi Penentuan Letak Lokasi Antena Terbaik Menggunakan Algoritma Fletcher-Powell - Ngarap Imanuel Manik Manik (Bina Nusantara University, 2011)
To meet the needs of information delivery to be rapid, mobile and safe needed a model calculation of the best antenna location and utilization of transmission media. One model that can be used takes advantages of wireless as well as models Flether-Powell algorithm, which combines mathematics with information technology. The algorithm can calculate the best position of a transmitter with reference of maximum received intensity amount in all the Main Point Coverage. To simplify the calculation process a computer program is developed written in Borland C. the program evaluation results show that by utilizing this application a company can place transmitters better and more effectively.